On a Nonlocal Multipoint and Integral Boundary Value Problem of Nonlinear Fractional Integrodifferential Equations. (28th October 2020) - Ibnelazyz, Lahcen; Guida, Karim; Melliani, Said; Hilal, Khalid
Abstract : The aim of this paper is to give the existence as well as the uniqueness results for a multipoint nonlocal integral boundary value problem of nonlinear sequential fractional integrodifferential equations. First of all, we give some preliminaries and notations that are necessary for the understanding of the manuscript; second of all, we show the existence and uniqueness of the solution by means of the fixed point theory, namely, Banach's contraction principle and Krasnoselskii's fixed point theorem. Last, but not least, we give two examples to illustrate the results.